Comparison of quality of life, anxiety, and depression levels based on acne vulgaris severity - Husna, Annisaul; Yenny, Satya Wydya; Desmawati, Desmawati; Akhyar, Gardenia; Masrul, Masrul; Yulistini, Yulistini (UI Scholars Hub, 2024)
Background: Acne vulgaris is a chronic inflammation of the pilosebaceous unit. Although acne vulgaris is not fatal, it can cause psychological effects. This study aimed to compare the quality of life, anxiety, and depression levels based on the severity of acne vulgaris among medical students at Andalas University. Methods: This was an observational-analytic study with a cross-sectional design. It was conducted from May to June 2023. The population included the third-grade students of the Medical Study Program of the Faculty of Medicine, Andalas University, who had acne vulgaris. The respondents were 70 people, recruited with consecutive sampling techniques. This research used Lehmann classifications to classify acne severity, the Cardiff Acne Disability Index (CADI) to assess quality of life, and the Depression Anxiety Stress Scale (DASS-21) to assess anxiety and depression. The statistical analysis used the Kolmogorov-Smirnov test. Results: Most female respondents, aged 20 years old, experienced mild acne vulgaris (84.3%). Additionally, the respondents predominantly had mild quality of life disorders (80%), normal anxiety level (32.9%), and normal depression level (52.9%). The Kolmogorov-Smirnov test found no relationship between the severity of acne vulgaris with quality of life (p = 0.076), anxiety level (p = 0.623), and depression level (p = 0.751). Conclusion: The results showed that most respondents had mild acne vulgaris, mild impairment in quality of life, normal anxiety level, and normal depression level. Statistical tests revealed no significant association between the severity of acne vulgaris and these variables.